Methylenedioxymethamphetamine (MDMA, 'Ecstasy'): Neurodegeneration versus Neuromodulation - Elena Puerta; Norberto Aguirre (MDPI AG, 2011)
The amphetamine analogue 3,4-methylenedioxymethamphetamine (MDMA, 'ecstasy') is widely abused as a recreational drug due to its unique psychological effects. Of interest, MDMA causes long-lasting deficits in neurochemical and histological markers of the serotonergic neurons in the brain of different animal species. Such deficits include the decline in the activity of tryptophan hydroxylase in parallel with the loss of 5-HT and its main metabolite 5-hydoxyindoleacetic acid (5-HIAA) along with a lower binding of specific ligands to the 5-HT transporters (SERT). Of concern, reduced 5-HIAA levels in the CSF and SERT density have also been reported in human ecstasy users, what has been interpreted to reflect the loss of serotonergic fibers and terminals. The neurotoxic potential of MDMA has been questioned in recent years based on studies that failed to show the loss of the SERT protein by western blot or the lack of reactive astrogliosis after MDMA exposure. In addition, MDMA produces a long-lasting down-regulation of SERT gene expression; which, on the whole, has been used to invoke neuromodulatory mechanisms as an explanation to MDMA-induced 5-HT deficits. While decreased protein levels do not necessarily reflect neurodegeneration, the opposite is also true, that is, neuroregulatory mechanisms do not preclude the existence of 5-HT terminal degeneration.